Genetic analysis of the Turkish gray wolf (Canis lupus) based on partial mitochondrial DNA sequences - İbiş, Osman; Aksöyek, Eren; Özcan, Servet; Keten, Akif; Yorulmaz, Tarkan; Tez, Coşkun (Vertebrate Zoology, 2016)
In this study, we focused on determining the genetic variability of Turkish gray wolves and also to reveal phylogenetic relationships of the Eurasian wolf populations using mitochondrial DNA sequences. Partial mitochondrial DNA sequences (440 bp) were obtained from 12 Turkish gray wolves, including D-loop region (332 bp). We found seven D-loop haplotypes (332 bp) among the 12 Turkish gray wolves. The D-loop sequences of the Turkish gray wolf were compared to sequences registered in GenBank from Eurasia under the name Canis lupus. Five Turkish haplotypes were shared with conspecific sequences from other regions of Eurasia in the species' range. Two haplotypes were unique for the Turkish wolves. The existence of shared haplotypes suggests that the gray wolves in Turkey and other regions might be originated from the same gene pool. The present study reports significant data for determining the genetic variability and revealing the phylogenetic relationships of Turkish gray wolves; it is suggested that the genetic variability of Turkish gray wolves is relatively high.